2009
DOI: 10.1097/aap.0b013e3181ac7d00
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors Predisposing to Coagulopathy in Patients Receiving Epidural Analgesia for Hepatic Surgery

Abstract: A high prevalence of hemostatic abnormalities in patients undergoing major hepatic resection while receiving epidural analgesia occurred. Important considerations may include discussion with the surgical team, measuring coagulation, and heightened clinical monitoring in the postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 12 publications
1
41
0
1
Order By: Relevance
“…Most studies to date on changes in the perioperative coagulation profile during hepatic surgery and epidural analgesia have not reported on chronic hepatic disease, defined as hepatic diseases of greater than 6 months' duration [5][6][7][8][9], or are limited by patient populations being restricted to healthy donors for donor hepatectomies [10][11][12][13]. However, patients with chronic hepatic diseases frequently require hepatic surgery, and hence are subject to the risks of abnormal postoperative coagulation profiles on epidural analgesia.…”
Section: Introductionmentioning
confidence: 96%
“…Most studies to date on changes in the perioperative coagulation profile during hepatic surgery and epidural analgesia have not reported on chronic hepatic disease, defined as hepatic diseases of greater than 6 months' duration [5][6][7][8][9], or are limited by patient populations being restricted to healthy donors for donor hepatectomies [10][11][12][13]. However, patients with chronic hepatic diseases frequently require hepatic surgery, and hence are subject to the risks of abnormal postoperative coagulation profiles on epidural analgesia.…”
Section: Introductionmentioning
confidence: 96%
“…Following hepatic resection, haemostatic disorders do occur, despite completely normal pre-operative coagulation function, and this may increase the risk of epidural haematoma [6,9]. It is controversial as to whether the benefits of thoracic epidural anaesthesia and analgesia, including excellent analgesia, decreased incidence of pulmonary complications and reduced duration of ileus, outweigh its potential risks such as epidural haematoma and increased administration of intravenous fluids [7,[10][11][12][13]. This review focuses on the safety and analgesic efficacy of the use of this technique in patients undergoing liver resection and also discusses the risk-benefit ratio of its use in the context of accelerated and enhanced recovery programmes.…”
mentioning
confidence: 99%
“…Although thoracic epidural anaesthesia and analgesia are commonly used for liver resection [3][4][5][6], there are concerns over its safety in this specific patient population. Complications associated with epidural catheters are uncommon, but include epidural haematomas, epidural abscesses or spinal cord injury [7,8]. Following hepatic resection, haemostatic disorders do occur, despite completely normal pre-operative coagulation function, and this may increase the risk of epidural haematoma [6,9].…”
mentioning
confidence: 99%
“…Mastuura et al [12]. suggested that a high postoperative PLT count was also a risk factor for decreased survival, and therefore the patient should be monitored for a high PLT count postoperatively [13,14] and proper treatment should be administrated when necessary.…”
Section: Discussionmentioning
confidence: 98%